Rethinking power, production, and social reproduction: Toward variegated social reproduction. (December 2019) - Bakker, Isabella; Gill, Stephen
This special issue introduces new work, new perspectives, and engages in a dialogue to revisit, extend and go beyond the original central hypothesis of Power, Production and Social Reproduction (2003). That volume and its primary hypothesis focused upon the unfolding contradiction between the global accumulation of capital and the provision of stable and progressive conditions of social reproduction. It hypothesized a growing contradiction between the intensified power of capital and many life-making/sustaining processes, including the condition of bodies and the biosphere. Our original hypothesis conceptualized capital accumulation and social reproduction as interlinked although within different and contradictory moments in the same system or totality. We add to this here the concept of variegated social reproduction which refers to the historical and ontological variability of social reproduction - and its specific differentiations and varieties in contemporary globalized capitalism - stemming from concrete social, cultural, ecological and material practices and structures. Indeed, as the articles in the special issue reflect, the neoliberalization and commodification of social reproduction remains incomplete and not all-encompassing or determinant. As such, the introduction and the special issue also suggest new research agendas.